Newness in Old Testament prophecy : an intertextual study - Leene, Henk. (Oudtestamentische Studiën, Old Testament Studies, 2013)
In Newness in Old Testament Prophecy: An Intertextual Study Henk Leene examines the relations between the new song raised in the Psalms, the new things concealed in Deutero-Isaiah, the new heaven and the new earth announced in Trito-Isaiah, Ezekiel's new heart and the new spirit, and the envisioned new creation and new covenant in Jeremiah. Where these promises were mainly linked form-critically, Henk Leene assumes their direct literary relations. In what direction does the one promise allude to the other, and how do such allusions draw us into a continuing intertextual dialogue on Israel's expectations about the future? Most challenging is Leene's conclusion that Jeremiah's promise of the new covenant presumes the newness passages from both Ezekiel and Isaiah.